High‐resolution stable isotope profiles from shells of the land snail Placostylus reveal contrasting patterns between snails originating from New Zealand and New Caledonia - Mathieu Quenu; Emily J. Judd; Mary Morgan‐richards; Steven A. Trewick; Katherine Holt; Jonathan Tyler; Andrew M. Lorrey (Journal of Quaternary Science, 2023)
The stable oxygen (δ 18 O shell ) and carbon (δ 13 C shell ) isotope ratios retrieved from the carbonate shell of terrestrial gastropods can be used as an environmental proxy and are thought to reflect dietary composition and ambient climatic conditions (e.g. precipitation amount, humidity, temperature). Here, we generate high‐resolution isotopic profiles of nine modern land snails of the genus Placostylus , collected from two locations in New Caledonia and one location in New Zealand. We found that snails from New Zealand had, on average, higher δ 18 O shell values than their counterparts in New Caledonia, which surprisingly runs counter to the expected relationship based on the isotopic composition of rainwater between these two regions. Specimens from New Caledonia exhibit ephemeral decreases in their δ 18 O shell values, which could be linked to extreme precipitation events in this region, while snails from New Zealand have less variation in their δ 18 O shell values. Snails from New Zealand had, on average, slightly higher δ 13 C shell than their counterparts in New Caledonia, but a large difference in carbon isotopes was sometimes observed between snails collected at the same location. Most snails exhibit a temporal trend in their δ 13 C shell values, indicating potential shifts in diet through to maturity.

Global warming leads to habitat loss and genetic erosion of alpine biodiversity - Fabio Leonardo Meza‐Joya; Mary Morgan‐Richards; Emily M. Koot; Steven A. Trewick (Journal of Biogeography, 2023)
Aim Species living on steep environmental gradients are expected to be especially sensitive to global climate change, but little is known about the factors influencing their responses to contemporary warming. Here, we investigate the influence of climate on the biogeography of three alpine species with overlapping ranges. Location Te Waipounamu (South Island) Aotearoa–New Zealand. Taxon Endemic alpine adapted Catantopinae grasshoppers. Methods We used niche modelling to estimate and project the potential niche of three focal species under past and future climate scenarios. Vulnerability assessments were performed using niche factor analyses. Demographic trends and phylogeographic structure were investigated using samples from 15 mountain tops to generate mitochondrial DNA haplotype networks and population genetic statistics. Results Niche models and genetic data suggest suitable habitat for all three alpine species was more widespread and contiguous in the past than today. Demographic analyses indicate in situ survival rather than post‐Pleistocene colonisation of current habitat. Population structuring and genetic divergence suggest that mountain uplift during the Pliocene and environmental barriers during Pleistocene glacial and interglacial stages shaped contemporary population structure of each species. Although geographically overlapping, niche analyses suggest these alpine species are not ecologically identical, each showing distinct responses to environmental change, but all will lose intraspecific diversity through population extinction. Main Conclusions Climatic, biological and geophysical factors controlled population structuring of three cold‐adapted species during the Pleistocene with a legacy of spatially separate intraspecific lineages. Ecological niche models for each species emphasise distinct combinations of environmental proxies, but all are expected to experience severe habitat reduction during climate warming. Increased global temperatures drive available habitat to higher elevation resulting in population contractions, range shifts, habitat fragmentation, local extinctions and genetic impoverishment. Despite alpine species not being ecologically identical, we predict all mountain biota will lose significant genetic diversity due to global warming.

SNAPSHOT USA 2020: A second coordinated national camera trap survey of the United States during the COVID ‐19 pandemic - Roland Kays; Michael V. Cove; Jose Diaz; Kimberly Todd; Claire Bresnan; Matt Snider; Thomas E. Lee; Jonathan G. Jasper; Brianna Douglas; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2022)
Managing wildlife populations in the face of global change requires regular data on the abundance and distribution of wild animals, but acquiring these over appropriate spatial scales in a sustainable way has proven challenging. Here we present the data from Snapshot USA 2020, a second annual national mammal survey of the USA. This project involved 152 scientists setting camera traps in a standardized protocol at 1485 locations across 103 arrays in 43 states for a total of 52,710 trap‐nights of survey effort. Most (58) of these arrays were also sampled during the same months (September and October) in 2019, providing a direct comparison of animal populations in 2 years that includes data from both during and before the COVID‐19 pandemic. All data were managed by the eMammal system, with all species identifications checked by at least two reviewers. In total, we recorded 117,415 detections of 78 species of wild mammals, 9236 detections of at least 43 species of birds, 15,851 detections of six domestic animals and 23,825 detections of humans or their vehicles. Spatial differences across arrays explained more variation in the relative abundance than temporal variation across years for all 38 species modeled, although there are examples of significant site‐level differences among years for many species. Temporal results show how species allocate their time and can be used to study species interactions, including between humans and wildlife. These data provide a snapshot of the mammal community of the USA for 2020 and will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, and the impacts of species interactions on daily activity patterns. There are no copyright restrictions, and please cite this paper when using these data, or a subset of these data, for publication.

SNAPSHOT USA 2019: a coordinated national camera trap survey of the United States - Michael V. Cove; Roland Kays; Helen Bontrager; Claire Bresnan; Monica Lasky; Taylor Frerichs; Renee Klann; Thomas E. Lee; Seth C. Crockett; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2021)
With the accelerating pace of global change, it is imperative that we obtain rapid inventories of the status and distribution of wildlife for ecological inferences and conservation planning. To address this challenge, we launched the SNAPSHOT USA project, a collaborative survey of terrestrial wildlife populations using camera traps across the United States. For our first annual survey, we compiled data across all 50 states during a 14‐week period (17 August–24 November of 2019). We sampled wildlife at 1,509 camera trap sites from 110 camera trap arrays covering 12 different ecoregions across four development zones. This effort resulted in 166,036 unique detections of 83 species of mammals and 17 species of birds. All images were processed through the Smithsonian’s eMammal camera trap data repository and included an expert review phase to ensure taxonomic accuracy of data, resulting in each picture being reviewed at least twice. The results represent a timely and standardized camera trap survey of the United States. All of the 2019 survey data are made available herein. We are currently repeating surveys in fall 2020, opening up the opportunity to other institutions and cooperators to expand coverage of all the urban–wild gradients and ecophysiographic regions of the country. Future data will be available as the database is updated at eMammal.si.edu/snapshot‐usa, as will future data paper submissions. These data will be useful for local and macroecological research including the examination of community assembly, effects of environmental and anthropogenic landscape variables, effects of fragmentation and extinction debt dynamics, as well as species‐specific population dynamics and conservation action plans. There are no copyright restrictions; please cite this paper when using the data for publication.

Loss and gain of sexual reproduction in the same stick insect - Mary Morgan‐Richards; Shelley S. Langton‐Myers; Steven A. Trewick (Molecular Ecology, 2019)
The outcome of competition between different reproductive strategies within a single species can be used to infer selective advantage of the winning strategy. Where multiple populations have independently lost or gained sexual reproduction it is possible to investigate whether the advantage is contingent on local conditions. In the New Zealand stick insect Clitarchus hookeri , three populations are distinguished by recent change in reproductive strategy and we determine their likely origins. One parthenogenetic population has established in the United Kingdom and we provide evidence that sexual reproduction has been lost in this population. We identify the sexual population from which the parthenogenetic population was derived, but show that the UK females have a post‐mating barrier to fertilisation. We also demonstrate that two sexual populations have recently arisen in New Zealand within the natural range of the mtDNA lineage that otherwise characterizes parthenogenesis in this species. We infer independent origins of males at these two locations using microsatellite genotypes. In one population, a mixture of local and nonlocal alleles suggested males were the result of invasion. Males in another population were most probably the result of loss of an X chromosome that produced a male phenotype in situ. Two successful switches in reproductive strategy suggest local competitive advantage for outcrossing over parthenogenetic reproduction. Clitarchus hookeri provides remarkable evidence of repeated and rapid changes in reproductive strategy, with competitive outcomes dependent on local conditions.

Closing the gap: Avian lineage splits at a young, narrow seaway imply a protracted history of mixed population response - Steve A. Trewick; Stephen Pilkington; Lara D. Shepherd; Gillian C. Gibb; Mary Morgan‐Richards (Molecular Ecology, 2017)
The evolutionary significance of spatial habitat gaps has been well recognized since Alfred Russel Wallace compared the faunas of Bali and Lombok. Gaps between islands influence population structuring of some species, and flightless birds are expected to show strong partitioning even where habitat gaps are narrow. We examined the population structure of the most numerous living flightless land bird in New Zealand, Weka ( Gallirallus australis ). We surveyed Weka and their feather lice in native and introduced populations using genetic data gathered from DNA sequences of mitochondrial genes and nuclear β‐fibrinogen and five microsatellite loci. We found low genetic diversity among extant Weka population samples. Two genetic clusters were evident in the mt DNA from Weka and their lice, but partitioning at nuclear loci was less abrupt. Many formerly recognized subspecies/species were not supported; instead, we infer one subspecies for each of the two main New Zealand islands. Although currently range restricted, North Island Weka have higher mt DNA diversity than the more wide‐ranging southern Weka. Mismatch and neutrality statistics indicate North Island Weka experienced rapid and recent population reduction, while South Island Weka display the signature of recent expansion. Similar haplotype data from a widespread flying relative of Weka and other New Zealand birds revealed instances of North Island—South Island partitioning associated with a narrow habitat gap (Cook Strait). However, contrasting patterns indicate priority effects and other ecological factors have a strong influence on spatial exchange at this scale.

Shifting ranges of two tree weta species ( H emideina spp.): competitive exclusion and changing climate - Mariana Bulgarella; Steven A. Trewick; Niki A. Minards; Melissa J. Jacobson; Mary Morgan‐Richards (Journal of Biogeography, 2014)
Aim Species' responses to climate change are likely to depend on their ability to overcome abiotic constraints as well as on the suite of species with which they interact. Responses to past climate change leave genetic signatures of range expansions and shifts, allowing inferences to be made about species' distributions in the past, which can improve our ability to predict the future. We tested a hypothesis of ongoing range shifting associated with climate change and involving interactions of two species inferred to exclude each other via competition. Location N ew Z ealand. Methods The distributions of two tree weta species ( H emideina crassidens and H . thoracica ) were mapped using locality records. We inferred the likely modern distribution of each species in the absence of congeneric competitors with the software Maxent . Range interaction between the two species on an elevational gradient was quantified by transect sampling. Patterns of genetic diversity were investigated using mitochondrial DNA , and hypotheses of range shifts were tested with population genetic metrics. Results The realized ranges of H . thoracica and H . crassidens were narrower than their potential ranges, probably due to competitive interactions. Upper and lower elevational limits on M ount T aranaki over 15 years revealed expansion up the mountain for H . thoracica and a matching contraction of the low elevation limits of the range of H . crassidens . The observed nucleotide diversity in H . thoracica was consistent with a species that persisted in northern areas during Pleistocene glacial periods, from where it expanded at warmer times. In contrast, a two‐tailed distribution of nucleotide diversity in H . crassidens was as expected for a species that expanded northwards during glacials and southwards during interglacials. Main conclusions Range shifts resulting from climate change involve complex species interactions. Competition among related species is an important factor limiting realized ranges. In N ew Z ealand, H . thoracica is likely to continue to displace H . crassidens as human‐induced global warming proceeds.

Geographic parthenogenesis and the common tea-tree stick insect of New Zealand - MARY MORGAN-RICHARDS; STEVE A. TREWICK; IAN A. N. STRINGER (Molecular Ecology, 2010)

Fewer species of Argosarchus and Clitarchus stick insects (Phasmida, Phasmatinae): evidence from nuclear and mitochondrial DNA sequence data - Steven A. Trewick; Julia Goldberg; Mary Morgan‐Richards (Zoologica Scripta, 2005)
The systematics of three genera of New Zealand stick insect in the subfamily Phasmatinae were investigated in light of inconsistencies in morphological variability within and among species. We sequenced a region of the mitochondrial genome, cytochrome oxidase (COI & COII; 1448 bp), and a nuclear marker, the internal transcribed spacers (ITS1 & ITS2; 1804 bp) from 49 stick insects. Mitochondrial DNA sequence divergences among the three genera ( Argosarchus , Clitarchus and Acanthoxyla ) were relatively high (∼12%) but the current taxonomy within genera was not supported. Within the three genera, low levels of genetic divergence were observed at both nuclear and mitochondrial loci, and phylogenetic analyses failed to support reciprocal monophyly of the two species in Argosarchus and Clitarchus . Sympatric individuals of Argosarchus spiniger and A. horridus were more closely related to each other than to members of their respective morphospecies from elsewhere. No males were found in the Chatham Island population of Argosarchus and although this population has been referred to as A. schauinslandi , genetic and morphological evidence does not support its distinction from mainland Argosarchus . Likewise, individuals identified as Clitarchus tuberculatus were genetically identical, or most similar to, C. hookeri from the same or adjacent sites rather then grouping with the stick insects they were morphologically most similar to. Lack of spatial, behavioural or ecological evidence concordant with the described species A. spiniger , A. schauinslandi and C. tuberculatus leads us to infer that these species are synonymies of A. horridus and C. hookeri respectively. We conclude that Argosarchus and Clitarchus have each been over‐split and actually consist of a single morphologically polymorphic, facultative parthenogenetic species. The genus Acanthoxyla with eight described species also has low levels of genetic divergence, similar to those found in Argosarchus and Clitarchus . A possible hybrid origin of Acanthoxyla involving its sister genus Clitarchus is implied by sharing of ITS sequence variants, but further sampling is needed before the species status of these obligate parthenogenetic lineages can be resolved. In contrast to some New Zealand Orthoptera, the Phasmatinae show little genetic variation suggesting coalescence in recent times, possibly reflecting lineage sorting in the Pleistocene.

Hybrid origin of a parthenogenetic genus? - MARY MORGAN‐RICHARDS; STEVEN A. TREWICK (Molecular Ecology, 2005)
The origin of the obligate‐parthenogenetic New Zealand stick insect genus Acanthoxyla was investigated using cytogenetics and sequencing of nuclear and mitochondrial DNA. Little mitochondrial DNA sequence variation (COI‐II) was found among seven species of the genus Acanthoxyla and we found no evidence for monophyly of the morphologically distinguished lineages. In contrast, two distinct clades of nuclear sequence (ITS) were obtained, one is restricted to the genus Acanthoxyla , while the other includes sequences obtained from its sister genus Clitarchus . Although Acanthoxyla appears to be diploid (2n = 36–38), it has two ill‐matched chromosome pairs. We hypothesize that two or more hybridization events involving the parental sexual species Clitarchus hookeri and an unknown taxon probably resulted in the formation of the parthenogenetic genus Acanthoxyla. However, the karyotype of Acanthoxyla bears little resemblance to the karyotype of the putative paternal species C. hookeri so the exact nature of Acanthoxyla remains in question.

After the deluge: mitochondrial DNA indicates Miocene radiation and Pliocene adaptation of tree and giant weta (Orthoptera: Anostostomatidae) - Steven A. Trewick; Mary Morgan‐Richards (Journal of Biogeography, 2005)
Aim New Zealand broke away from the margins of Gondwana c . 75 Ma. Since then, New Zealand taxa derived from the Gondwanan biota are thought to have been exposed first to a subtropical climate on a low lying terrain, then severe land reduction during the Oligocene marine transgression, followed by much cooler climates of the Pliocene and Pleistocene, at which time mountain ranges emerged. The biological consequence of New Zealand's geological and climatic history is not well understood, in particular the extent to which the Oligocene acted as a biological bottleneck remains unresolved. Methods We used mitochondrial cytochrome oxidase I and 12S DNA sequences to examine the extent of diversity and inferred timing of speciation of New Zealand weta (Anostostomatidae), a group of Orthoptera with a Gondwanan distribution generally thought to be ancient inhabitants of New Zealand. Main conclusions We hypothesize that at least three distinct groups of weta survived the Oligocene marine transgression and radiated subsequently. Speciation followed during the Miocene and radiation into new habitats occurred during the Pliocene when mountain building created novel environments. Patterns of genetic diversity within species reflect, in some instances, geographical subdivision in the Pliocene, and in other cases, Pleistocene range changes resulting from climate change.